The small RNA SgrS controls sugar–phosphate accumulation by regulating multiple PTS genes - Rice, Jennifer B. (Oxford University Press, 2011)
A number of bacterial small RNAs (sRNAs) act as global regulators of stress responses by controlling expression of multiple genes. The sRNA SgrS is expressed in response to glucose–phosphate stress, a condition associated with disruption of glycolytic flux and accumulation of sugar–phosphates. SgrS has been shown to stimulate degradation of the ptsG mRNA, encoding the major glucose transporter. This study demonstrates that SgrS regulates the genes encoding the mannose and secondary glucose transporter, manXYZ. Analysis of manXYZ mRNA stability and translation in the presence and absence of SgrS indicate that manXYZ is regulated by SgrS under stress conditions and when SgrS is ectopically expressed. In vitro footprinting and in vivo mutational analyses showed that SgrS base pairs with manXYZ within the manX coding sequence to prevent manX translation. Regulation of manX did not require the RNase E degradosome complex, suggesting that the primary mechanism of regulation is translational. An Escherichia coli ptsG mutant strain that is manXYZ(+) experiences stress when exposed to the glucose analogs α-methyl glucoside or 2-deoxyglucose. A ptsG manXYZ double mutant is resistant to the stress, indicating that PTS transporters encoded by both SgrS targets are involved in taking up substrates that cause stress.